A Network Pharmacology Analysis of Secondary Metabolites of Noni (Morinda citrifolia) as Immunomodulators - M. Helmi; Ahmad Shobrun Jamil; M. Artabah Muchlisin; Irsan Fahmi Almuhtarihan (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
Immunomodulators are substances or compounds that can modulate or help increase the activity and function of the immune system. The medicinal use of herbal plants is now increasing again among Indonesian people. Noni (Morinda citrifolia) is a plant commonly found in Indonesia that has long been known to have many benefits for treating and preventing various diseases and the secondary metabolites have potential as immunomodulators. This study aimed to determine the protein network associated with the body's immune system, which was activated by the administration of noni. The explorative descriptive research was conducted with in silico analysis using a computational model with software, including KNApSAck, Dr. Duke, Pubchem, Swiss ADME, Swiss Target Prediction, Gene Cards, Venny, STRING, and KEGG. Based on the results of pharmacological network analysis, noni contains 128 secondary metabolites, and 83 of them have high bioavailability. Based on pharmacological network analysis, (z,z,z)-8,11,14-eicosatrienoic-acid and 1-5-6-trihydroxy-anthraquinone are important compounds that play a role in the immune system because they are expected to interact with five crucial pathways related to immunomodulators.